Doing Good : Racial Tensions and Workplace Inequalities at a Community Clinic in El Nuevo South - Deeb-Sossa, Natalia (Book collections on Project MUSE., 2013)
Throughout the "New South," relationships based on race, class, social status, gender, and citizenship are being upended by an influx of Latina/o residents. This book examines these issues as they play out in the microcosm of a community health center in North Carolina that previously had served mostly African American clients, but now serves predominantly Latina/o clients. Drawing on eighteen months of experience as a participant-observer in the clinic and in-depth interviews with clinic staff at all levels, the author provides an informative and fascinating view of how changing demographics are profoundly affecting the new social order. All of the healthcare workers want to be seen as "doing good." But they fail to see how, in constructing and maintaining their own moral identity in response to their personal views and stereotypes, they have come to treat each other and their clients in ways that may contradict their ideals.